2020
DOI: 10.1044/2020_jslhr-19-00320
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processes Underlying Nonword Rhyme Differentiate Eventual Stuttering Persistence and Recovery

Abstract: Purpose Phonological skills have been associated with developmental stuttering. The current study aimed to determine whether the neural processes underlying phonology, specifically for nonword rhyming, differentiated stuttering persistence and recovery. Method Twenty-six children who stutter (CWS) and 18 children who do not stutter, aged 5 years, completed an auditory nonword rhyming task. Event-related brain potentials were elicited by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Inefficient use of declarative memory systems in developmental stuttering may also be indicated by differences in neural processes for unfamiliar, novel, or nonword stimuli in children who eventually persist in stuttering compared to children who eventually recover and children who do not stutter. This is supported by a series of studies that performed retrospective analyses of data from 5-years-olds, when all children who stutter were stuttering (Gerwin & Weber, 2020; Hampton Wray & Spray, 2020). Findings revealed that children who eventually persisted in stuttering exhibited less mature nonword rhyme processing compared to children who eventually recovered and children who do not stutter (Hampton Wray & Spray, 2020).…”
Section: Declarative Memory In Stutteringmentioning
confidence: 84%
See 3 more Smart Citations
“…Inefficient use of declarative memory systems in developmental stuttering may also be indicated by differences in neural processes for unfamiliar, novel, or nonword stimuli in children who eventually persist in stuttering compared to children who eventually recover and children who do not stutter. This is supported by a series of studies that performed retrospective analyses of data from 5-years-olds, when all children who stutter were stuttering (Gerwin & Weber, 2020; Hampton Wray & Spray, 2020). Findings revealed that children who eventually persisted in stuttering exhibited less mature nonword rhyme processing compared to children who eventually recovered and children who do not stutter (Hampton Wray & Spray, 2020).…”
Section: Declarative Memory In Stutteringmentioning
confidence: 84%
“…This is supported by a series of studies that performed retrospective analyses of data from 5-years-olds, when all children who stutter were stuttering (Gerwin & Weber, 2020; Hampton Wray & Spray, 2020). Findings revealed that children who eventually persisted in stuttering exhibited less mature nonword rhyme processing compared to children who eventually recovered and children who do not stutter (Hampton Wray & Spray, 2020). Importantly, when semantic context was available to support the declarative memory system, children who eventually persisted in stuttering exhibited comparable rhyme processing to children who eventually recovered and children who do not stutter (Gerwin & Weber, 2020).…”
Section: Declarative Memory In Stutteringmentioning
confidence: 84%
See 2 more Smart Citations
“…In an experimental task, CWS in the Purdue cohort who remained persistent used strategies in creating rhymes that differed from those of typically fluent and recovered children (Gerwin et al, 2019). Finally, atypicalities in cortical processing of rhyming/nonrhyming words were detected in Purdue cohort persistent CWS (Gerwin & Weber, 2020; Hampton Wray & Spray, 2020; Mohan & Weber, 2015).…”
Section: Language Factors That Appear To Influence Recovery From Earl...mentioning
confidence: 92%